The concept of geo-demographic situation and geo-demographic typology of the subjects of the Russian Federation. - Fedorov, Gennady (Bulletin of Geography. Socio-economic Series, 2014)
The article presents the results of research on typologisation of Russian regions according the geo-demographic situation. The typologisation of regions is performed on the basis of statistics for 2011-2012. The regions are described through demographic, economic, social, settlement, ecological, and ethno-demographic categories, the most common of which according to the authors point of view are the typological features of the geo-demographic situation. The subjects of the Russian Federation provided the research material to apply 15 typological traits and identify three types of geo-demographic situation, 9 subtypes of the first level, sub-types of the second level and a model subtype of the third level. The study shows that various types and subtypes of regions require different approaches in demographic, economic, social, equity, ethnic, environmental, and population distribution regional policies towards relevant entities of the Russian Federation.